Revisiting the Legacy of Islamic Legal Scholarship: The Influence of Sharia on Contemporary Legal Systems - Salman Faris LC (Mabadi Iqtishad Al Islami, 2025)
This study explores the enduring legacy of Islamic legal scholarship and its significant influence on both historical and contemporary legal systems, with a particular focus on the multifaceted nature of Sharia. The research addresses the issue of misunderstanding Islamic law as rigid and outdated by highlighting its historical adaptability and intellectual richness. The primary objective is to examine how Islamic jurisprudence, particularly through the principles of Maqasid al-Shariah, has shaped legal systems and continues to inform debates on justice, human rights, and legal pluralism. Utilizing a qualitative library research methodology, the study analyzes classical Islamic legal texts, juristic methodologies, and modern interpretations to trace the evolution of Sharia from its foundational sources—the Quran and Hadith—to its integration into systems like the Ottoman and Mughal legal frameworks. The findings reveal that Sharia is not merely a codified set of rules, but a comprehensive ethical system responsive to context through tools such as Ijtihad, Qiyas, and Istislah. Moreover, the influence of Islamic law extends beyond the Muslim world, contributing to discourses on legal pluralism and ethical governance globally. Ultimately, the study demonstrates the continued relevance of Islamic legal tradition in shaping contemporary legal and moral thought in Muslim-majority societies and beyond.